SPIRITUAL SCOUTCRAFT: METHODS DEPLOYED FOR RELIGIOUS CHARACTER VALUES INTEGRATION AT PONTIANAK'S ISLAMIC-BASED ELEMENTARY SCHOOLS - Erinda, Hayyu; Imron, Ali; Sunarni, Sunarni (Jurnal Visi Ilmu Pendidikan, 2024)
This research explores methods for integrating religious values in scouting, focusing on interaction dynamics, challenges, and solutions at SDIT Al-Mumtaz. Using a case study and qualitative methods (Miles, M.B, Huberman, A.M, Saldana, 2014), it condenses data stages, emphasizing diverse tailored methods aligned with scouting levels, integration goals, and student needs. Collaborative mentor efforts, flexibility, and adaptability are crucial. Intensive participant-facilitator interaction significantly impacts religious character values implementation. Facilitators, as "mothers" and "leaders," act as instructors and role models, fostering two-way communication for skill development and understanding. Challenges include fear management, student understanding variations, designing entertaining and educational scouting activities, social pressure, and differing participant skills. Despite challenges, SDIT Al-Mumtaz mentors successfully employ planned approaches and high commitment